The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.2174/1874091x01711010036
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cysteine Ubiquitylation Sites on the Sec23A Protein of the COPII Complex Required for Vesicle Formation from the ER

Abstract: Background:COPII is a multiprotein complex that surrounds carrier vesicles budding from the Endoplasmic Reticulum and allows the recruitment of secretory proteins. The Sec23a protein plays a crucial role in the regulation of the dynamics of COPII formation ensuring the proper function of the secretory pathway.Objective:Since few evidences suggest that ubiquitylation could have a role in the COPII regulation, the present study was aimed to establish whether the Sec23a component of the vesicular envelope COPII c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Ubiquitination may also regulate mammalian Sec23. Recently, the Remondelli group reported the unusual monoubiquitination of human Sec23A on two cysteine residues, C432 and C449 ( Amodio et al, 2017 ). These residues may be functionally important for COPII trafficking, as the authors report that a C→A mutation at either site reduces Sec23A occupancy at ERES in cultured mammalian cells, though the mechanisms and consequences of these proposed PTMs remain to be confirmed in trafficking assays ( Amodio et al, 2017 ).…”
Section: Background and Copii Overviewmentioning
confidence: 99%
“…Ubiquitination may also regulate mammalian Sec23. Recently, the Remondelli group reported the unusual monoubiquitination of human Sec23A on two cysteine residues, C432 and C449 ( Amodio et al, 2017 ). These residues may be functionally important for COPII trafficking, as the authors report that a C→A mutation at either site reduces Sec23A occupancy at ERES in cultured mammalian cells, though the mechanisms and consequences of these proposed PTMs remain to be confirmed in trafficking assays ( Amodio et al, 2017 ).…”
Section: Background and Copii Overviewmentioning
confidence: 99%
“…It has been demonstrated that circulating total microparticles are greatly elevated in patients with T2DM, suggesting that changing microparticle levels are possibly relevant to diabetic conditions [ 43 ], thus opening a new scenario for future investigations. Recently, it has also been demonstrated that Sterol regulatory element-binding protein 1 (SREBP1)—an important transcriptional regulator of lipogenesis [ 44 ], regulated by Sec23A [ 45 ]—is involved in the modulation of insulin resistance and in the lipogenesis that is chronically enhanced diabetes, thus laying the foundation for the development of novel future therapeutic strategies to contain the onset of diabetes.…”
Section: Endothelial Dysfunction and Diabetesmentioning
confidence: 99%
“…Indeed, in driving vesicle formation, COPII ensures by Sec24 isotypes that only folded transmembrane proteins or soluble cargo molecules are sorted and packaged by specific cargo receptors, respectively. The flux of COPII vesicle carriers exiting the ER is regulated by different factors according to secretory demand (Subramanian et al, 2019) or to the ER stress conditions, in which the abundance of COPII vesicles is reduced, giving rise to alterations in cargo secretion and structural defects of post-ER compartments (Amodio et al, 2009;Amodio et al, 2013;Amodio et al, 2017).…”
Section: The Upr and The Multitasking Control Of Protein Foldingmentioning
confidence: 99%